Cow's milk allergy in Dutch children: an epigenetic pilot survey. Issue 1 (December 2016) - Petrus, Nicole; Henneman, Peter; Venema, Andrea; Mul, Adri; Sinderen, Femke; Haagmans, Martin; Mook, Olaf; Hennekam, Raoul; Sprikkelman, Aline; Mannens, Marcel
Abstract Background Cow's milk allergy (CMA) is a common disease in infancy. Early environmental factors are likely to contribute to CMA. It is known that epigenetic gene regulation can be altered by environmental factors. We have set up a proof of concept study, aiming to detect epigenetic associations specific with CMA. Methods We studied children from the Dutch EuroPrevall birth cohort study (N = 20 CMA, N = 23 controls, N = 10 tolerant boys), age and gender matched. CMA was challenge proven. Bisulfite converted DNA (blood) was analyzed using the 450K infinium DNA-methylation array. Four groups (combined, girls, boys and tolerant boys) were analysed between CMA and controls. Statistical analysis and pathway-analysis were performed in "R" using IMA, Minfi and the global-test package. Differentially methylated regions inDHX58, ZNF281, EIF42A and HTRA2 genes were validated by quantitative amplicon sequencing (ROCHE 454® ). Results General hypermethylation was found in the CMA group compared to control children, while this effect was absent in the tolerant group. Methylation differences were, among others, found in regions ofDHX58, ZNF281, EIF42A and HTRA2 genes. Several of these genes are known to be involved in immunological pathways and associated with other allergies. Conclusion We show that epigenetic associations are involved in CMA. Although, the statistical power of our study is limited and our sample was based on whole blood, we were still able to detect feasible loci and pathways. Therefore our findings might contribute to future diagnostic or therapeutic interventions for specific CMA. Further studies have to confirm the findings of our study.